Pratiques paysannes et utilisation potentielle de Metarhizium flavoviride Gams and Rozsypal en lutte antiacridienne au Niger - Maiga, I.H.; Douro-Kpindou, O.K.; Lomer, C.J.; Langewald, J. (Springer, 1999)
A socio-economic study was executed in South East Niger to determine the conditions under which a novel mycopesticide based on the fungus Metarhizium flavoviride could be introduced for locust and grasshopper control as a possible alternative reducing the use of synthetic chemicals. From the interviews, all farmers estimated locusts and grasshoppers to be one of three major pests. The survey revealed that 93.8% of the farmers conduct collective pesticide applications. About 45.5% of the farmers received support from the brigades, at least once. The remaining farmers (54.5%) were not assisted by the brigades due to a lack of pesticides. Farmers estimate that the choice of any pesticide greatly depends upon its knock-down ability (57.5%) or the numbers of cadavers found after a treatment (42.5%). Most farmers (82%) consider the government to be responsible for locust and migrant grasshoppers control. On average, farmers were willing to pay US$ 1.00 per ha per year, to protect their crops.